The Influence of Madden–Julian Oscillation on Local-Scale Phenomena over Indonesia during the Western North Pacific and Australian Monsoon Phases - Pramuwardani, Ida; Hartono, Hartono; Sunarto, Sunarto; Sopaheluwakan, Ardhasena (Forum Geografi, 2018)
In this study, geographical Madden–Julian oscillation (MJO) propagation in association with precipitation rate was obtained using lag correlation applied to empirical orthogonal function (EOF) analysis modes 1 and 2 of filtered MJO data. The precipitation rate over Indonesia was provided at day -10 through day +10 in five-day steps during the December, January, and February (DJF) Western North Pacific (WNP) and July, August and September (JAS) Australian (AU) monsoon phases. Connection with local atmospheric factors was then sought through comparison of local precipitation, represented by 3-hourly precipitation, and dynamical processes, represented by multilevel wind, at seven locations across Indonesia. The results show a global MJO contribution toward local-scale phenomena in Tangerang, Surabaya, and Makassar during the DJF-WNP monsoon phase and in Padang, Medan, Surabaya, Makassar, and Kupang during the JAS-AU monsoon phase. Meanwhile, a lack of MJO contribution toward local factors is presumably due to other local through wider atmospheric-scale phenomena which are suspected to have more influence, particularly in Medan, Padang, Manado, and Kupang during the DJF-WNP monsoon phase, and in Manado and Tangerang during the JAS-AU monsoon phase. This research uses a dataset of 15-year series of daily and three-hourly Tropical Rainfall Measuring Mission (TRMM) (3B42 V7 derived) measurements, 850 hPa zonal wind measurements from 30-year reanalysis data from the ERA-Interim reanalysis dataset, and a 15-year series of 12-hourly observational soundings data from seven stations of the Indonesian Meteorological Climatological and Geophysical Agency (BMKG).